Transvenosus, a new genus in the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with description of one new species - Wang, Yang; Zhang, Yalin (Zootaxa, 2015)
Evacanthinae is a small subfamily in the Cicadellidae (Young, 1968; Zhang, 1990). It was redefined by Dietrich (2004), who included the tribes Evacanthini, Nirvanini, Balbillini and Pagaroniini in this subfamily. Recently, a new species was found in loaned material from Thailand, having several peculiar features worthy of establishing a new genus, described below. In addition, based on study of specimens collected from the type locality, Cunedda signuma Li & Webb is transferred to the new genus.